KARAKTERISTIK TINDAKAN TIPPEE DALAM PRAKTIK INSIDER TRAIDING PADA PASAR MODAL INDONESIA - Putu Eva Ditayani Antari; I Gusti Agung Ayu Mas Triwulandari (Widya Yuridika, 2019)
The practice of insider trading is a very neat offense, the object it is working on has been planned carefully and carried out gradually, so it is certainly understandable that to catch the culprit is not an easy matter. Oversight of the Financial Services Authority on the actions of insider trading actors may prevent insider trading practices by certain parties, especially the unregulated tippee (legal vacuum) in the Capital Market Law. This research is a type of normative juridical research by raising legal issues concerning the characteristics of tippee actions in the practice of insider trading on the capital market in Indonesia. The results of the study found that to be a tippee regulated in the Capital Market Law, it is necessary to have an "effort" from the tippee itself to get inside information, whether by acting against the law or not. From this arises a weakness in the arrangement regarding insider or parties that are prohibited from conducting securities transactions. The weakness is that it does not regulate tippees who get insider information passively (not doing business). Tippees who are prohibited from conducting securities transactions are active tippees who, on their own initiative, seek insider information, where: a). The information is sought by breaking the law, such as by stealing, persuading, violence, or threats, or). The information is with restrictions (such as confidentiality obligations). So the advice that can be given is that it should be made more stringent arrangements related to tippee actions in order to create legal protection against tippee actions in insider trading which is very detrimental to investors. Legal protection is in the form of making legal rules that are fair and dynamic because by enforcing and making legal rules that are fair and dynamic, it will create an investor's trust to invest their capital in the Indonesian capital market.